Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s10815-018-1157-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of day 2 versus day 3 embryo transfer on early pregnancy outcomes in women with a low yield of fertilized oocytes

Abstract: Our findings suggest that transferring embryos on D2 versus D3 in women with a limited number of 2PN stage zygotes does not affect early pregnancy outcomes. These results indicate that there can be some flexibility in scheduling the day of transfer at the convenience of both the patient and the center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…3 Sacha et al suggested that transferring embryos on D2 versus D3 in women with a low number of fertilized oocytes ( two 2PN-stage zygotes) does not affect early pregnancy outcomes. 7 A prospective, randomized trial conducted by Shahine et al did not show a difference in the pregnancy outcome between D2 and D3 embryo transfer in poor responders. 8 However, their definition of poor responders was vague.…”
Section: Introductionmentioning
confidence: 92%
“…3 Sacha et al suggested that transferring embryos on D2 versus D3 in women with a low number of fertilized oocytes ( two 2PN-stage zygotes) does not affect early pregnancy outcomes. 7 A prospective, randomized trial conducted by Shahine et al did not show a difference in the pregnancy outcome between D2 and D3 embryo transfer in poor responders. 8 However, their definition of poor responders was vague.…”
Section: Introductionmentioning
confidence: 92%
“…All aspects of the artificial reproductive technology (ART) process have benefited from this effort: ovarian hyper‐stimulation protocols, 2 embryo culture conditions, 3 , 4 embryo transfer procedures, 5 , 6 and embryo freezing techniques 7 , 8 have been improved. The choice of embryo to be transferred is based on either morphological criteria at D2 (day 2 post fertilization), 9 at D3, 10 or at the blastocyst stage, 11 or on preimplantation genetic diagnosis (PGD) techniques. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%